Perancangan Media Pembelajaran Berbasis Website Pada Mata Kuliah Renang PJKR Universitas Muhammadiyah Muara Bungo - Nuraini, fadila; Maulana Putra, Ikhsan; Bani Pilitan, Raja (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
The background of this research is based on the importance of utilizing technology in the world of education, especially in creating learning media that is interactive, easily accessible, and able to support students' understanding of swimming material independently. This study aims to design website-based learning media for swimming courses in the Physical Education, Health and Recreation (PJKR) Study Program at Universitas Muhammadiyah Muara Bungo (UMMUBA). The research method used is research and development (Research and Development) with the ADDIE model (analysis, design, development, implementation, and evaluation). The subjects in this study were 28 people consisting of 25 PJKR students in semester 2 in swimming courses, 2 swimming lecturers in semester 2, and 1 admin from the study program secretary. The trial results show that the media has a functionality success rate of 0.9855, which means that the features function properly as designed. Meanwhile, the results of the usability test showed a user acceptance rate of 88.86%, which indicates that this media is classified as very feasible from a user perspective.The conclusion of this research is that the website-based learning media designed has met the eligibility standards both in terms of functionality and usability, and can be used as an alternative support in the learning process of swimming courses in the PJKR UMMUBA environment.